Embryonic development capacity of bovine oocytes aspired by ovum pick-up and from slaughterhouse ovaries - Quispe, Carlos Enrique (2018)
The aim of this study was to compare the capacity of embryonic development of oocytes recovered from slaughterhouse ovaries and recovered in vivo by guided ultrasound (ovum pick-up – OPU) in an in vitro production system. Nine sessions in 59 Holstein cows were done to obtain oocytes through OPU and 408 ovaries were collected from 204 cows in the slaughterhouse. For the in vitro maturation of oocytes, only those of grade 1 and 2 were used, matured and fertilized using MIV, FIV and CIV® medium until day 7. The recovery rate of oocytes, grade 1 and 2 oocytes and the percentage of embryos (blastocysts) produced in vitro on day 7 were evaluated. The recovery rate of oocytes collected from slaughterhouse ovaries was higher as compared with oocytes collected by OPU (10.0 vs. 7.2 oocytes per session/cow, p<0.05). There was a greater number of viable oocytes of grade 1 and 2 when the collection was from slaughterhouse ovaries (7.6 vs. 3.4 oocytes per session/cow, p<0.05). The blastocyst rate was 30.5 and 20.8% with slaughterhouse ovarian oocytes and OPU, respectively (p<0.05). A greater capacity to develop oocytes retrieved from slaughterhouse ovaries was obtained than those recovered by ovum pick-up.